Factors affecting secondary school teachers’ willingness to deliver Sexual Reproductive Health (SRH) education in Malaysia - Goh, Yee Shan; Foo, Hor Yern (2019)
Sexual Reproductive Health (SRH) education has long been integrated into educational system yet it seemed lack of effectiveness as reflected in the rising rate of social issues such as teenage pregnancies. Past studies put more emphasis on students’ sexual knowledge and behavior while study reveal on teaching perspective remain scarce. This study investigated perceived knowledge, comfort to teach, and self-efficacy on secondary school teacher’s willingness to deliver SRH education in Malaysia. Quantitatively study with cross-sectional design using multistage cluster sampling method was used to recruit respondents for this study. A total of 252 secondary school teachers (Mage: 39.37; SDage: 7.83; 78.6% female; 82.5% Malay; 11.9% Chinese; 4.4% Indian; and 1.2% other ethnicities) whom taught Biology, Science, and PJK from central regions (i.e., Perak, Selangor, and Kuala Lumpur) of Peninsular Malaysia participated in this study. The result indicated that there was significant positive relationship between perceived knowledge, comfort to teach, self-efficacy, and willingness to teach. Comfort to teach was found to be the only predictor to explain willingness to teach. However, there was no significant differences between male and female in their willingness to teach. Hence, comprehensive teachers’ training aiming in advancing teachers’ professional development in teaching SRH education should emphasize in providing standardize knowledge transfers skills, enhancing selfefficacy, and comfort to teach which to equip the teachers as an effective agent of change in SRH among adolescents in Malaysia.